SMART2D—development and contextualization of community strategies to support self-management in prevention and control of type 2 diabetes in Uganda, South Africa, and Sweden. Issue 1 (3rd February 2020) - Absetz, Pilvikki; Van Olmen, Josefien; Guwatudde, David; Puoane, Thandi; Alvesson, Helle Mölsted; Delobelle, Peter; Mayega, Roy; Kasujja, Francis; Naggayi, Gloria; Timm, Linda; Hassen, Mariam; Aweko, Juliet; et al.
Abstract : When developing programs to help patients with type 2 diabetes or its risk factors to manage their condition better, it is important to take into account the cultural context of the patients while also retaining the active ingredients that make the programs effective. Abstract: Type 2 diabetes (T2D) and its complications are increasing rapidly in low- and middle-income countries, as well as among socioeconomically disadvantaged populations in high-income countries. Support for healthy lifestyle and self-management is paramount but not well implemented in health systems, and there is need for knowledge on how to design and implement interventions that are contextualized and patient centered and address special needs of disadvantaged population groups. The SMART2D project implements and evaluates a lifestyle and self-management intervention for participants recently diagnosed with or being at increased risk for T2D in rural communities in Uganda, an urban township in South Africa, and socioeconomically disadvantaged urban communities in Sweden. Our aim was to develop an intervention with shared key functions and a good fit with the local context, needs, and resources. The intervention program design was conducted in three steps facilitated by a coordinating team: (a) situational analysis based on the SMART2D Self-Management Framework and definition of intervention objectives and core strategies; (b) designing generic tools for the strategies; and (c) contextual translation of the generic tools and their delivery. This article focuses on community strategies to strengthen support from the social and physical environment and to link health care and community support. Situational analyses showed that objectives and key functions addressing mediators from the SMART2D framework could be shared. Generic tools ensured retaining of functions, while content and delivery were highly contextualized. Phased, collaborative approach and theoretical framework ensured that key functions were not lost in contextualization, also allowing for cross-comparison despite flexibility with other aspects of the intervention between the sites. The trial registration number of this study is ISRCTN11913581.